How much sunlight does it take to disinfect a boardroom?: a short history of executive compensation regulation - Ian Dew-Becker (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper reviews the history of executive compensation disclosure and other government policies affecting CEO pay, and as well surveys the literature on the effects of these policies. Disclosure has increased nearly uniformly since 1933. A number of other regulations, including special taxes on CEO pay and rules regarding votes on some pay packages have also been introduced, particularly in the last 20 years. However, there is little solid evidence that any of these policies have had any substantial impact on pay. Policy changes have likely helped drive the move towards more use of stock options, but there is no conclusive evidence on how policy has otherwise affected the level or composition of pay. I also review evidence from overseas on Say on Pay, recently proposed in the US, which would allow nonbinding shareholder votes on CEO compensation. The experiences of other countries have been positive, with tighter linkages between pay and performance and improved communication with investors. Mandatory say on pay would be beneficial in the US.
Keywords: J01; J08; J33; K22; 330; Führungskräfte; Vergütungssystem; Regulierung; Auskunftspflicht; Wirtschaftspolitische Wirkungsanalyse; Gehalt; USA